Pengaruh Kecerdasan Intelektual, Kecerdasan Emosional, Kompetensi dan Lingkungan Kerja pada Kinerja Auditor - Pratiwi, Ni Luh Yuni; Suryanawa, I Ketut (E-Jurnal Akuntansi, 2020)
The purpose of this study is to obtain empirical evidence about the influence of intellectual intelligence, emotional intelligence, competence and work environment on auditor performance. This research was conducted at the Public Accounting Firm (KAP) in Bali. The population in this study are all auditors who work at KAP in Bali. The sample of this study was 55 respondents, carried out with saturated sampling technique. The data used are primary data with data collection methods namely questionnaires. The data analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that intellectual intelligence, emotional intelligence, competence and work environment have a positive effect on auditor performance. The results of this study as input for the leadership of the Public Accounting Firm in seeking better performance, and for the auditor can be used as evaluation material to maintain and improve performance in conducting audits. Keywords: Intellectual Intelligence; Emotional Intelligence; Competence; Work environment; Auditor Performance.